Rethinking growth orientation: Do ski-resorts' strategies fit the profiles of today's alpine skiers? - Thomas Bausch; Florian Ortanderl; Ulrike Pröbstl-Haider (International Journal of Tourism Research, 2024)
The strategy and marketing of ski resorts in the European Alps are still characterized by growth orientation and the extension of technical snow production to ensure high snow reliability. In contrast, this study hypothesizes that besides a high-performing ski resort, winter ski vacationists have further expectations for activities during their stay varying by their skiing skill level and personal preferences. The present study surveys 1413 Alpine ski tourists to identify their daily routines, activities, and used ski resort services. The findings uncover significant differences in the activity profiles with six clearly distinguishable guest segments. The results highlight the need for custom-tailored product development considering the complete set of winter experiences as well as pricing strategies that specifically target the identified segments. Furthermore, the findings underline that ski resort and destination managers need to include daily changes in snow and weather conditions in their strategies considering climate and demographic change.
Keywords: 330; climate change; crowding; pricing; skier segmentation; snow quality; winter vacation